The Plasmin Inhibitors of Plasma - Shamash, Y; Rimon, A (Thrombosis and Haemostasis, 1964)
A new method for the assay of plasmin inhibitors in human plasma is described. The method consists of determination of the caseinolytic activity of a standard plasmin solution before and after incubation with the inhibitor, with lysine added to the mixture as a stabilizer of plasmin. Using this method, it was found that plasma contains enough inhibitors to inactivate 30 caseinolytic units of plasmin, or 10 times the normal amount of plasminogen in human plasma.